Analisis Sistem Rekrutmen Karyawan pada Rumah Sakit Wava Husada Kepanjen Malang (Studi Kualitatif Deskriptif) - Roinul Ainiyah; Adita Nafisah (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Employee recruitment is one of the strategic functions in human resource management at health service institutions. This study aims to analyze and describe in depth the employee recruitment system implemented at Wava Husada Hospital, Kepanjen, Malang. The method used is descriptive qualitative research with a case study approach. Data were collected through in-depth interviews with key informants consisting of the Head of Human Resources, recruitment committee members, and employees who had gone through the recruitment process. Direct observation and documentation study were also conducted to obtain comprehensive data. The results show that Wava Husada Hospital implements a structured open recruitment system with three main stages: (1) administrative selection covering verification of document completeness and applicant qualification compliance; (2) psychological tests designed to measure applicants' intelligence, personality, and value alignment with organizational culture; and (3) interviews involving a multidisciplinary team to assess technical and non-technical competencies of prospective employees. This recruitment system has proven effective in selecting competent healthcare workers committed to excellent service. However, several obstacles were also found, including the limited number of applicants from certain specializations and technical constraints in the online recruitment information system. This study recommends strengthening employer branding strategies and improving the human resource management information system capacity at Wava Husada Hospital.